A novel microsurgery robot mechanism with mechanical motion scalability for intraocular and reconstructive surgery. Issue 3 (21st March 2021) - Yang, Un‐Je; Kim, Duksang; Hwang, Minho; Kong, Dukyoo; Kim, JoonHwan; Nho, Young‐Hoon; Lee, WonKi; Kwon, Dong‐Soo
Abstract: Background: Intraocular surgery and reconstructive surgery are challenging microsurgery procedures that require two types of motion: precise motion and larger motion. To effectively perform the requisite motion using a robot, it is necessary to develop a manipulator that can adjust the scale of motion between precise motion and less precise, yet larger motion. Aims: In this paper, we propose a novel microsurgery robot using the dual delta structure (DDS) to mechanically scale the motion to seamlessly adjust between precise and larger motion. Materials & Methods: The DDS forms a lever mechanism that enables the motion scaling at the end‐effector using two delta platforms. Seamless scale adjustment enables the robot to effectively perform various surgical moves. Results: A prototype robot system was developed to validate the effectiveness of the DDS. The experiment results in various scale settings validated the scaling mechanism of the DDS. Conclusion: Through a graphical simulation and measurement experiment, the robot's precision level and attainable workspace has been confirmed adequate for intraocular and reconstructive surgery.